REVIEW ON INSTRUMENTS USED FOR MEASURING THE CIRCULAR/ ROUND JOBS IN INDUSTRY - Mr. Niteen Shivaji Mali; Mr. Dhairyashil Ashok Naik (International Engineering Journal For Research & Development, 2023)
Measuring tools are most important in any industry as they make the life of society the better and safer by giving them acceptable products. Recently numbers of method are being used to inspect the diameter of components. But still in all types of industry from small unit to big unit for measurement of diameter mostly used instruments are Vernier calliper and Micrometre. This paper emphases on different types of vernier calliper and Micrometre used on machine shop.